1001 Flotation non-wearing and wearing in occupational boating fatalities, Canada 1991–2010. (1st September 2016) - Barss, Peter; Olsen, Karlyn; Hamilton, Jane; Dalke, Shelley
Abstract : Background: Flotation wearing is low among Canadian boating fatalities. The study ascertained trends and factors associated with non-wearing of flotation among occupational boating victims in Canada, and compared with recreational victims. Methods: Annual Red Cross collection of 1991-2010 Canadian coroner data by structured questionnaire. Analysis included activity, purpose, personal, equipment, environment factors, trends. Results: There were 10, 511 water-related deaths, 9, 961 from immersion including drowning and cold, 513 trauma, and 37 other injuries. Excluding land and air transport, 37% of immersions involved boating. 12% (n = 366) of 3324 boating deaths involved occupation and 85% recreational or daily life. Occupational boating immersions included 297 drownings, 53 drownings with hypothermia, 5 deaths due to hypothermia complicated by drowning, and 11 hypothermia deaths. At least 55% involved very cold water less than 10 °C. 62% were commercial fishing and 14% marine shipping; 9% of fishers and 12% of shipping victims were properly wearing a flotation device. Overall, 11% were properly wearing, 2% improperly wearing, and at least 35% not wearing flotation, possibly more since flotation was unknown for 38%. For 9% flotation was absent in the boat, and for 55% unknown. Range of boats in violation of current regulations, with no flotation, ranged from 9 to 64%, with many unknowns. Incidents included 31% capsizes, 27% falls overboard, and 25% swamping; only 5% dying falling overboard wore flotation, 9% in capsizes, 17% in swamping. There was no trend in non-wearing during surveillance. Most deaths occurred in Nova Scotia, British Columbia, and Newfoundland/Labrador. Numbers of deaths declined from 246 during 1991–2000 to 120 during 2001–2010. For recreational deaths, a flotation device was worn properly by 12%; in ≥50% flotation was absent, representing violation of current regulations requiring in boats, even if wearing is not required. Conclusions: While occupational deaths have declined, for various reasons, non-wearing of flotation among victims remains high. Legislation on wearing varies and is left to discretion of the operator. Review of various boating interventions has found the greatest effectiveness to be legislation mandating wearing, coupled with effective enforcement. Hypothermia protective garments may also be required in cold water conditions, frequent in the Canadian context, especially for occupational boating.